Applied research on heart rate variability in monitoring sports fatigue of boxing athletes - Wang, J.; Qiu, J.; Chen, S. (Exercise Biochemistry Review, 2018)
Objective Based on the diagnosis of sports fatigue using physiological and biochemical indicators, to detect the changes of heart rate variability (HRV) index before and after heavy load training in boxing athletes, and observe the effect of heavy load training on cardiac autonomic nerves. The purpose of this study was to investigate the application of HRV to monitor boxing athletes` sports fatigue.